Navigating energy diplomacy in times of recovery and conflict: A study of cross-border energy trade dynamics - Gökçe, Osman Zeki; Hatipoğlu, Emre; Belaïd, Fateh (Elsevier Ltd, 2024)
Recent geopolitical crises have underlined the importance of understanding when and how energy interdependence affects international politics. While scholars have extensively debated the link between international politics and international trade in general terms, systematic analyses gauging how energy interdependence shapes interstate relations have recently begun to emerge. To facilitate research on this topic, this study asks whether energy relations between states shape their foreign policy decisions. Using the recently released Global Energy Relations Dataset and United Nations General Assembly Voting Data, our study shows strong support for the hypothesis that energy interdependence increases dyadic foreign policy affinity. Moreover, out of four primary energy resources (i.e. coal, oil, natural gas, and electricity), trade in oil appears to be a strong motivator for trading states' foreign policy preferences to converge.
Keywords: Global Conflicts; Geopolitics; Gas; Oil; Diplomacy; Energy Security; Energy Transition